A Perceived Organizational Support dengan Employee Engagement: Perceived Organizational Support dengan Employee Engagement pada Karyawan Depo PT Z - Augusty, Hijriyah; Hurriyati, Dwi (IDEA: Jurnal Psikologi, 2025)
ABSTRACT   In carrying out their duties, employees experience various kinds of challenges. The biggest challenge is work accidents. However, employees remain involved in the company. The purpose of this research is to determine the relationship between Perceived Organizational Support and Employee Engagement among PT Z employees. This research method is quantitative by collecting data using a questionnaire on the Employee Engagement scale with Perceived Organizational Support. The subjects in this research were 161 employees. The sampling technique used in this research is purposive sampling. The data analysis technique used is validity and reliability testing. The data analysis method in this research is two-stage, namely testing assumptions/prerequisites and testing hypotheses. The results of research conducted on PT Z employees using the Perceived Organizational Support variable (independent variable) and the Employee Engagement variable (dependent variable) show that this variable has an effective contribution of 54.8%, which means there is acceptance of the proposed hypothesis and 45.2%. The remaining % is influenced by other factors outside those studied. Based on the results obtained from data analysis and discussion, the researcher concluded that there is a relationship between Perceived Organizational Support and Employee Engagement among PT Z employees.